2022
DOI: 10.1002/cctc.202101828
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationships in Highly Active Platinum‐Tin MFI‐type Zeolite Catalysts for Propane Dehydrogenation

Abstract: Pt/Sn-containing MFI zeolites prepared by one-pot hydrothermal methods are highly active and selective catalysts for propane dehydrogenation. An alternative preparation method is reported alongside an in-depth characterization of Pt and Sn before and after reaction. Pt species dispersed on highlydefective Silicalite-1 show a significantly long catalytic lifetime with an improved coke resistance, but increased PtÀ Sn alloying and the (eventual) build-up of carbon leads to deactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In other words, nonselective propane cracking is faster than selective dehydrogenation of propane over the fresh active sites (at the initial reaction stage), whereas this trend is reversed once the coke is deposited on the surface of GaN nanocrystallites. Together with the dependence of GaN particle size on the catalytic activity and apparent activation energy, it can be proposed that the overall CO 2 -ODHP reaction was structure sensitive over nanostructured GaN, which was probably related to the potential presence of other structure-sensitive reactions (e.g., DDP, CO 2 hydrogenation, and reverse Boudouard). …”
Section: General Discussionmentioning
confidence: 99%
“…In other words, nonselective propane cracking is faster than selective dehydrogenation of propane over the fresh active sites (at the initial reaction stage), whereas this trend is reversed once the coke is deposited on the surface of GaN nanocrystallites. Together with the dependence of GaN particle size on the catalytic activity and apparent activation energy, it can be proposed that the overall CO 2 -ODHP reaction was structure sensitive over nanostructured GaN, which was probably related to the potential presence of other structure-sensitive reactions (e.g., DDP, CO 2 hydrogenation, and reverse Boudouard). …”
Section: General Discussionmentioning
confidence: 99%
“…Some researchers believe that SnO x promotes dehydrogenation by acting as an electron donor, transferring electrons to Pt and changing its electronic state. [20][21][22] This in turn is beneficial to propene desorption, thereby increasing the propene selectivity. Xiong et al 23 thought that formation of small PtSn clusters allows the catalyst to achieve high propene selectivity due to the facile desorption of propene.…”
Section: Sn Promotermentioning
confidence: 99%
“…4), which revealed the improved Pt dispersity induced by the geometric effect. 56 The SMSI effect between Pt and SnO 2 on the structural features and catalytic activity of the catalyst under targeted reaction conditions has been systematically studied. 57 The results indicated that the geometric effect contributed greatly to the dehydrogenation activity than the electronic effect.…”
Section: Development Of Pdh Catalystsmentioning
confidence: 99%
“…Beale et al designed the defective functional group of silanol and framework of Sn( iv ) for achieving an exceptional Pt dispersion by means of the geometric constraint properties from zeolite micropores. 56 Owing to the specific function of confinement, a series of modifications on supports could improve the performance of catalysts in the PDH reaction, and provided a new consideration to guide the rational design of exceptional PDH catalysts.…”
Section: Advanced Synthetic Strategies For Catalyst Designmentioning
confidence: 99%
See 1 more Smart Citation